(untitled) (Journal of the College of Education for Women, 2023)
This paper addresses the new coloring in the concept of dystopian society as represented by the positive role of one of the characters vs. the passive role of the government and its mutual effect on the people of the society. In addition, it describes how all men in the dystopian society victimize and degrade the other through unlawful acts, like: stealing, rape, and fear, which are the lowest points in a moral decay. However, it offers hope by illustrating a positive sense, as exemplified by the doctor’s wife out of Saramago’s optimistic view that men may be descended from good women. Accordingly, the paper aims to examine the effect of the government’s role in the lives of the people who have later turned into blind in a dystopian society and of people towards one other, and to clarify the positive sense as represented by the doctor’s wife. To meet this, the researcher is to adopt Tom Moylan’s (2000) concept of Dystopia when analyzing José Saramago’s novel, Blindness. This study has uncovered the erosion of trust in others and clarified the heinous injustices committed by both authority figures and laypeople. The troops’ cruel treatment toward the blind has led to their sudden infection with that disease. Saramago expressed his upbeat belief that men can change just, they derived from good women as the doctor’s wife. The study further has exposed the impact of the violent behavior of both the government and the people towards one another on the confusion and degradation of the humanity.